Gender and the history of religion. New approaches and recent studies - Saurer, Edith (Kvinder, Køn & Forskning, 2005)
The article consists of two parts. In the first it gives an insight into the historiography concerning gender and religion primarily in Austria and Germany since the 19th century for the last twenty years about. Researches on religious women’s movements are discussed exemplarily as well as the debate on the ‘feminization of religion’, which had an great impact on studies on religion in the last years. The second part of the text discusses religious conversions as an example for interreligious (gender) relationships taking into account the longlasting ban on interreligious marriages. The example concerns the conversion of the romantic Dorothea Schlegel, of her husband Friedrich Schlegel and her two sons of the first marriage (Philipp and Johannes (Jonas) Veit) and analyses the conversion narratives of her writings.